Pengambilan Keputusan di Perguruan Tinggi Pesantren di Universitas Ibrahimy Sukorejo Situbondo dan Universitas Nurul Jadid Paiton Probolinggo - Syuhud, Syuhud (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
The purpose of the study was to describe the decision-making process, participation in decision-making, and decision-making methods at Ibrahimy Sukorejo University Situbondo and Nurul Jadid University Paiton Probolinggo. The research methodology is a qualitative study, the type is descriptive with a multi-site design at the Sukorejo Islamic boarding school in Situbondo and the Nurul Jadid Islamic boarding school in Paiton Probolinggo. Data collection technique; Observations, interviews, and documentary studies. The data were organized, interpreted, tested for validity by triangulation procedures, then analyzed using the interactive model of Milles and Huberman. The findings of this study are: (1) the decision-making process is carried out by identifying the problem, developing it by conducting internal and external analysis, solving it with a new strategy, implementing and evaluating the results of the decision; (2) forms of participation are ideas, thoughts, suggestions, criticisms, and energy in carrying out organizational tasks according to the structure. And the factors that influence participation are the factors of intention, sincerity, dedication, age, knowledge, and a sense of responsibility in carrying out organizational tasks to achieve goals; (3) the decision-making methods are autocratic decisions, consultative decisions, joint decisions, and religious intuitive decisions.